Performance Optimization of Polres Sukoharjo Safety Security Units Through Traffic Community Education in Order to Reduce Fatality Traffic Accidents (Indonesian Journal of Police Studies, 2024)
Traffic accidents are a serious problem throughout the world, including in Indonesia, especially in the Sukoharjo Police area. Traffic accidents that occur often result in fatalities or death. According to WHO, the 3rd biggest cause of death after HIV/AIDS and tuberculosis is traffic accidents which have touched 2.4 million people per year worldwide. Of course this is very concerning and a concern for the Indonesian Police Traffic Units, especially the Traffic Security and Safety Unit. The research method for writing this Final Project uses a qualitative approach chosen by the author in this paper because it allows for a deeper look at the social phenomena that occur in the field. By using this method, the author can collect high-quality data and get a deeper understanding of the issues discussed. In addition, qualitative methods allow authors to provide solutions that are more appropriate and in accordance with actual needs. In explaining the results of writing, a qualitative approach also provides flexibility for the writer to explain in more detail and describe aspects that are relevant to the phenomenon being observed. Writing this Final Project uses contextual literature to explore the problems in writing this Final Project, namely Management Theory to find out the management of the Kamsel Unit implementing Dikmas Then, Theory of Organizational Resources to find out the organizational resources of the Kamsel Unit to implement Dikmas So, Optimization Concepts, Then Dikmas Concepts, Concepts Fatality, the Concept of Operational Management of Police Activities and the Concept of Traffic Accidents. The Sukoharjo Polres Satlantas Kamsel Unit has carried out pre-emptive efforts including carrying out Dikmas Then activities to schools in Sukoharjo Regency related to orderly traffic, carrying out traffic information via Top.FM radio broadcasts, implementing traffic order from an early age with Friendly Police activities Children also build cooperation with related agencies to jointly reduce traffic accident fatalities in the Sukoharjo Police area.
Keywords: FATALITAS; UNIT KAMSEL; DIKMAS LANTAS